Perilaku Lentur Kolom yang Diretrofit Menggunakan Wire Mesh dan Self Compacting Concrete Akibat Beban Siklik: Flexural Behaviour of Retrofit Column Using Wire Mesh and Self Compacting Concrete Due to Cyclic Load - Satar, Syahrul; Limbongan, Joey; Firman, Risman; Febry Fitriani Sofyan, Yanny; Tamsil Yunus, Ahmad; Munadrah; Widiasari Maruddani, Andi (CV Insight Publisher, 2024)
Results of experimental and analytical study of the flexural behavior of retrofitted columns using wiremesh and SCC concrete due to cyclic loading. The purpose of this study was to analyze the strength of the column retrofitted using wiremesh and SCC due to cyclic loading. The test object consisted of 3 columns with a size of 300x300 mm, consisting of a control column (KK), a total reinforcement column (KR-1) and a reinforcement column in the approximate plastic hinge region (KR-2). From the test results, the flexural strength of the reinforced column is higher than that of the unreinforced column. The rate of increase in strength of KR-1 compared to KK is 46.68% in compression and 37.87% in tension. The rate of increase in the strength of KR-2 compared to the compressive load of KK is 41.71%, and the tensile load is 32.35%.